A family of Ru(ii) complexes built on a novel sexipyridine building block: synthesis, photophysical properties and the rare structural characterization of a triruthenium species1. Issue 25 (7th July 2015) - Laramée-Milette, Baptiste; Lussier, Félix; Ciofini, Ilaria; Hanan, Garry S.
<x xml:space="preserve">Abstract</x> A new sexipyridine ligand and its Ru(ii) family of complexes is described along with its characterization by electrochemical and photophysical methods as well as a rare X-ray analysis of a triruthenium polypyridine complex.